1998
DOI: 10.1093/gerona/53a.3.b161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging and Food Restriction on the Antioxidant Enzyme Activity of Rat Livers

Abstract: The effects of aging and food restriction on the activities and mRNA levels of antioxidant enzymes in rat livers were examined. Rats were fed ad libitum every day (AL) or ad libitum on every other weekday (FR). At 30 months of age, the catalase and glutathione peroxidase activities were lower, whereas the thiobarbituric acid (TBA) value, an index of lipid peroxidation of the AL rats, was higher than that at younger ages. At 33 months of age, copper/zinc superoxide dismutase (CuZnSOD), catalase, and glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 21 publications
3
27
0
1
Order By: Relevance
“…Studies measuring 8-hydroxy-2Ј-deoxyguanosine as a marker of DNA oxidative damage have reported that differences emerge between control and CR animals at either 23 mo of age in mice (54) or 30 mo of age in rats (32). Studies of lipid peroxidation in liver have also reported differences between control and CR rats only after the animals reached 30 mo of age (18). Similarly, a study measuring protein carbonyl content in liver from rats reported that significant age-related increases in protein oxidative damage did not occur until the animals were 24 mo old (58).…”
Section: Discussionmentioning
confidence: 99%
“…Studies measuring 8-hydroxy-2Ј-deoxyguanosine as a marker of DNA oxidative damage have reported that differences emerge between control and CR animals at either 23 mo of age in mice (54) or 30 mo of age in rats (32). Studies of lipid peroxidation in liver have also reported differences between control and CR rats only after the animals reached 30 mo of age (18). Similarly, a study measuring protein carbonyl content in liver from rats reported that significant age-related increases in protein oxidative damage did not occur until the animals were 24 mo old (58).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that SOD is a general stress-response factor, one possible but undefined explanation for the increase in SOD in the non-exposed controls might be due to stress arising from their being held in captivity. Another possibility is the starvation-caused alteration of AOE profiles in liver, since food deprivation or starvation has been known to be one of the factors to increase the formation of ROS as reported in both teleosts and mammals (Gomi and Matsuo 1998;Pascual et al 2003;Nam et al 2005). Expression of SOD in aquatic organisms has been known to be significantly affected by a variety of stressors or stimuli, including pathogen infections, exposure to toxic pollutants, nutritional restriction and thermal stress (see Zelko et al 2002).…”
Section: Expression Analysis Of Shark Cu Zn-sod Transcriptsmentioning
confidence: 99%
“…In contrast, red crabs collected during C3 had elevated TBARS levels and relatively lower levels of antioxidant enzymes, suggesting an oxidative stress process in red crabs during the autumn of 2006. Decreased antioxidant levels are commonly found under food restriction conditions (Gomi andMatsuo 1998, Bayir et al 2011). Elevated TBARS levels in the absence of increased O 2…”
Section: Discussionmentioning
confidence: 99%